Uma leitura da ambiguidade em Memorial de Aires, de Machado de Assis - Gomes, Francisco de Assis (2010)
This present research has as main objective to apprehend in the book Memorial de Aires, the last novel from Machado de Assis, the construction of ambiguity. As a segment to the dissertation we have used as a north the following questions: in what measure the ambiguity presents itself as multidirectional when representing, in the novel, the human being as inconclusive and also undefined?; Until what level, the metalanguage, the intertextuality and the modalizing resources work as structural recourses in the ambiguity construction?; How does the implicit author arrange such resources in a way to give unity to a text that is notably marked by the lack of unity? To develop these proposals, we have used as basis some theoretical and critical propositions from researchers like: Mikhail Bakhtin, Antoine Compagnon, Gilberto Pinheiro Passos, Samira Chalhub. From some of the conclusions that we have realized in the analysis, we have apprehended that in the architecture of Machado s discourse through the character Conselheiro Aires there are multiples senses registered and this can configure the ambiguity in different modes